Precise aftershock activity in the marine source region of the 2024 Noto-Hanto earthquake by rapid response observation using ocean bottom seismometers - Masanao Shinohara; Ryota Hino; Tsutomu Takahashi; Koichiro Obana; Shuichi Kodaira; Ryosuke Azuma; Tomoaki Yamada; Takeshi Akuhara; Yusuke Yamashita; Eiji Kurashimo; Yoshio Murai; Takehi lsse; et al. (Earth, Planets and Space)
Abstract The 2024 Noto-Hanto earthquake with a magnitude of 7.6 occurred in the Noto Peninsula on January 1, 2024. The mainshock had a reverse fault focal solution and direction of compression axis was the northwest–southeast. In the Noto Peninsula, earthquake swarms have been observed since December 2020. In contrast to this swarm activity, the mainshock had extending to the marine area. Therefore, we performed a rapid response seafloor seismic observation in the source region and its vicinity. We deployed 34 free-fall pop-up type ocean bottom seismometers (OBSs) in January 2024, recovered 26 short-period OBSs (SPOBSs) after a month. The arrival times of the P- and S-waves were manually read from the data of SPOBSs and land seismic stations based on the event list by a land seismic network. We relocated the hypocenters of the events by combination of the location programs using absolute travel times with station corrections and the double-difference method. A velocity model was derived from the velocity structure by the marine seismic survey. Focal mechanisms were estimated using the grid search method based on the polarities of the first Pwave arrivals. The aftershock depths mostly ranged from 0.2 km to 17 km. Although the aftershock activity seems to be confined in the upper crust, relatively deep events occurred in the easternmost source region. The aftershocks formed several dipping planes corresponding to the multiple faults described in the offshore active fault model constructed before the mainshock. The upper boundaries of the planes of the hypocenter distribution coincide with the upper edges of the modeled faults, and the lower boundary of the aftershock distribution also aligns well with the lower edges of the faults. This consistency indicates that the rupture at the mainshock propagated to faults with different geometries. Although 70 events had a reverse fault focal mechanism similar to the mainshock, we identified 87 strike-slip events. Most of the events involving both reverse and strike-slip faults had P-axes perpendicular to the fault strike. This finding suggests that the aftershock activity was affected by a northwest–southeast compressional stress. Graphical Abstract